Mental health and COVID-19 in South Africa. (June 2021) - Nguse, Siphelele; Wassenaar, Douglas
COVID-19, the disease caused by severe acute respiratory syndrome coronavirus 2, has affected most parts of the globe since its first appearance in the city of Wuhan, China, in December 2019. As a result, the World Health Organization declared the virus a global public health crisis and a pandemic within 2 weeks, after the virus had spread to 114 countries with 118 000 recorded cases and 4291 deaths due to the virus and related complications. The World Health Organization declaration is indicative of the enormous impact of the pandemic on human life globally. South Africa has not been exempted from that impact. While the pandemic has affected all South Africans in various ways, the poor have been most affected due to structural inequality, poverty, unemployment, and lack of access to quality health care and other services. Furthermore, public mental health has also been negatively affected by the pandemic, and this comes against a backdrop of an ailing mental health care system. We argue that the psychology profession, as a mental health profession and behavioural science, working as part of a multidisciplinary team, ought to play a significant role in addressing the mental health ramifications of the pandemic. In so doing, lessons can be drawn from other countries while establishing contextual immediate and long-term interventions.